2022
DOI: 10.23887/jet.v6i1.42738
|View full text |Cite
|
Sign up to set email alerts
|

Student Perception of Online Learning Media Platform During the Covid-19 Pandemic

Abstract: Learning during the Covid-19 Pandemic requires lecturers to be able to adapt by using online learning platforms. As a result, there are different perceptions of students regarding the effectiveness of each of these platforms. The study aimed to analyze differences in students' perceptions about the effectiveness of using WhatsApp, Google Classroom, and Zoom platforms. This research method uses quantitative methods to measure the level of perception and is combined with qualitative methods to analyze student pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In line with the study which found the digital platforms that are most often used to support learning, especially when in the network (hybrid), namely WhatsApp groups, video conferences, and the use of Google facilities such as Google Classroom [29]- [31]. One of the reasons for choosing the use of WhatsApp, video conference, and Google Classroom is because it utilizes the technology that has been provided and is quite familiar [32]- [34]. The use of WhatsApp group, video conference, and Google Classroom is an option other than because the features that are indeed free also tend to be familiar to use because previously teachers have received training, especially in utilizing Google features.…”
Section: Resultsmentioning
confidence: 66%
“…In line with the study which found the digital platforms that are most often used to support learning, especially when in the network (hybrid), namely WhatsApp groups, video conferences, and the use of Google facilities such as Google Classroom [29]- [31]. One of the reasons for choosing the use of WhatsApp, video conference, and Google Classroom is because it utilizes the technology that has been provided and is quite familiar [32]- [34]. The use of WhatsApp group, video conference, and Google Classroom is an option other than because the features that are indeed free also tend to be familiar to use because previously teachers have received training, especially in utilizing Google features.…”
Section: Resultsmentioning
confidence: 66%
“…The reality is that in learning history at school, there are still many kinds of problems that occur when learning history is less attractive to students, because it is considered boring and less useful learning, because the study is only theoretical and also only discusses material in the past. have no future goals (Fadli et al, 2022;Fahruddin et al, 2022). Based on the results of preliminary observations conducted by researchers at MAN 1 Bandar Lampung, they got information that the interest in learning history by students tends to be low because the media used by teachers to teach is only from printed books and also some from the internet sources using the lecture method.…”
Section: Introductionmentioning
confidence: 99%
“…The learning process is carried out using the group presentation method and theoretical discussion which only uses the lecture method and only uses improvised learning media to make the learning process, in addition to the limited lecture time. The emergence of problems in learning history must be addressed properly by the teacher, one of which is by developing learning media (Fahruddin et al, 2022;Sastranegara et al, 2020;Setiawan et al, 2020;Setiawan & Aman, 2018;Soni et al, 2018). Moreover, it is supported by the fact that there is a lot of material during the Hindu-Buddhist period in Indonesia, which makes students tend to have to quickly grasp the material given.…”
Section: Introductionmentioning
confidence: 99%